Bilateral comparison of barbell kinetics and kinematics during a weightlifting competition - Rossi, S. J.; Buford, T. W.; Smith, D. B.; Kennel, R.; Haff, E. E.; Haff, G. G. (International Journal of Sports Physiology and Performance, 2007)
The primary purpose of this study was to simultaneously analyze both ends of the barbell with 19 weightlifters (age 18.0 ± 3.2 years, body mass 84.0 ± 14.2 kg, height 167.3 ± 8.7 cm) participating in a weightlifting competition to determine whether there were asymmetries in barbell kinematics and kinetics between the right and left sides of the barbell. The second purpose was to compare barbell-trajectory classification of the snatch and clean lifts between the right and left sides of the barbell. Methods: Barbell kinematic and kinetic data were collected and analyzed with 2 VS-120 weightlifting-analysis systems (Lipman Electronic Engineering Ltd, Ramat Hahayal, Israel). Barbell trajectories (A, B, and C) for the right and left sides were analyzed for each lift. Results: No significant difference was found in trajectory classification between sides of the barbell for either lift. The frequencies analysis revealed that type C barbell trajectories were the most prevalent in each lift. When the right and left sides of the barbell were compared during the snatch and clean, no significant differences were determined for any kinematic or kinetic variables. Conclusions: The V-scope system appears to facilitate analysis of barbell kinematics, kinetics, and trajectories during weightlifting competition regardless of which side of the barbell is analyzed.